The Determinants of Farmers' Entrepreneurial Intention in Tanzanian Agricultural Sector: : A Structural Modeling Approach - Tambwe, M. A.; Chachage , Bukaza L.; Mbise, E. R. (Advances in Social Sciences Research Journal, 2020)
This paper aims to clarify the determinants of entrepreneurial intention of orange farmers in Muheza, Tanzania by validating the extended theory of planned behaviour (TPB) developed by Ebewo, Rugimbana & Shambare, (2017). In these days where entrepreneurial development is seen as the core contributor to enhance business and facilitate economic development, the best possible determinants of entrepreneurial determinants are required. The survey was conducted to 349 small scale orange farmers in Muheza. To test the model, the constructs of entrepreneurship training, farmers’ attitudes, subjective norms, perceived behaviour control and entrepreneurial intention inputs were validated followed by factor analysis and structural equation modeling. results show the positive and significant influence of perceived behaviour control, attitudes towards entrepreneurship as the significant determinants in the development of orange farmers’ entrepreneurial intention. Further, the findings validate the developed intentional entrepreneurship training model and enhances the body of knowledge by highlighting the key skills required by farmers in entrepreneurship training programmes. It was also found that, entrepreneurial intention of orange farmers was predicted by attitudes and perceived behaviour control but not subjective norms. To inculcate and increase orange farmers’ entrepreneurial intention, the government and policy makers should focus on cultivating positive attitudes and perceived behaviour control so that to spread positive stance to entrepreneurship in order to enhance the willingness of orange farmers to engage in commercial farming.